State capitalism how the return of statism is transforming the world - Kurlantzick, Joshua (New York Oxford University Press, 2016)
The end of the Cold War ushered in an age of American triumphalism best characterized by the "Washington Consensus:" the idea that free markets, democratic institutions, limitations on government involvement in the economy, and the rule of law were the foundations of prosperity and stability. The last fifteen years, starting with the Asian financial crisis, have seen the gradual erosion of that consensus. Many commentators have pointed to the emergence of a powerful new rival model: state capitalism. In state capitalist regimes, the government typically owns firms in strategic industries. Not beholden to private-sector shareholders, such firms are allowed to operate with razor-thin margins if the state deems them strategically important. China, soon to be the world's largest economy, is the best known state capitalist regime, but it is hardly the only one.
Keywords: Government ownership--Developing countries